2015
DOI: 10.1007/s15010-015-0778-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasite infections and associated clinical symptoms among patients with end-stage renal disease undergoing hemodialysis

Abstract: The current study revealed a high prevalence of intestinal parasites and related clinical symptoms in ESRD patients undergoing hemodialysis. Since hemodialysis patients are immunocompromised and intestinal parasites can cause serious clinical complications, we suggest that stool examination for intestinal parasites, with an emphasis on detection of Cryptosporidium spp. and Blastocystis, should be incorporated into the routine clinical care for these patients. Measures for preventing the acquisition of IPIs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 30 publications
4
50
0
5
Order By: Relevance
“…In this study, no significant relationship between the prevalence of intestinal parasites and sex was observed in patients referred to the laboratory, which was consistent with results of some other studies in the world and Iran (25,29,(31)(32)(33). A significant association between sex and parasites infection has been reported in Kashan (27).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, no significant relationship between the prevalence of intestinal parasites and sex was observed in patients referred to the laboratory, which was consistent with results of some other studies in the world and Iran (25,29,(31)(32)(33). A significant association between sex and parasites infection has been reported in Kashan (27).…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate that the helminthic infection has declined compared to previous studies in Iran (6,12,(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 43%
“…Some researchers have shown that the transport of oxygen to the brain and decrease in blood stream may act as a mechanism in the complex etiology of AD (28). This study was conducted with regards to the localization of T. gondii tissue cysts in the central nervous system and reports indicating the impact of T. gondii on neurodegenerative diseases (7,9,10,13,16,29,30), as well as the lack of information about the prevalence of toxoplasmosis in patients with AD in studies conducted on the prevalence of parasitic infections in Lorestan province (18,19,(31)(32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…Dialysis adequacy is concept rather than a number (35); thus, the main drawback of Kt/V is the use of limited data for measuring a concept that can be affected by multiple factors (36). This type of concept cannot be gauged based on serial evaluation of the blood urea or investigation of the amount of removal of urea and the built up fluids in the blood (37).…”
Section: Discussionmentioning
confidence: 99%